(3fXQjI GdJCejf GdJYGhfj (B: s (3OQGSI ebGQfI Hjf GdTQjYI GdESdGejI hGdbGfhf GdhVYj (B/ s - (3QLH YHO GdJhGH SdjeGf cOhGfjs; (3YHO GdhOhO jMji (B: s; (3jhSa bGSe (B: s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1986)
(3JHOC gPg GdQSGdI HJegjO Yf eYfi GdebGQfI Hjf GdTQjYI GdESdGejI hGdbGfhf GdhVYj, Ke JfbSe Edi GdbSe GdChd Yf GdJCejf HhLg YGe, Ke GdbSe GdKGfj GdJCejf GdJYGhfj(B.s
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, (B1986.s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI UaMGJ (B946 - 981.s
Keywords: (3GdbGfhf GdeOfjs; (3GdJCejf GdJYGhfjs; (3GdJCejfs; (3CbSGe GdJCejfs; (3YbO GdJCejfs; (3GdJCejf GdESdGejs; (3JCejf GdLHQs; (3JCejf GdcaGjIs; (3GdJCejf GdJHGOdjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs